Learning Outcomes: How is the FERA Learning Model Experimentation in Islamic Religious Education Learning? - Nadya Ranialini; Erlando Dimas Dwi Putra; Eva Amelia; Istiqomah Istiqomah; Halimatus Sadiyah; Nurul Azizah (Action Research Journal Indonesia (ARJI), 2025)
Teachers who frequently rely on lecturing as a teaching method often cause students to become passive in class and struggle to understand the material. As a result, student learning outcomes tend to decline. Traditional teaching models such as lectures and assignments often have minimal impact on improving students’ academic performance. This study aims to analyze the experimentation of the Focus, Explore, Reflect, Apply (FERA) learning model in enhancing students’ learning outcomes in Islamic Religious Education (PAI) at SMP Negeri 29 Bandar Lampung. The FERA learning model encourages students to be active, think critically, reflect, and apply knowledge in their daily lives. This research used a quantitative approach with a quasi-experimental design. The sample consisted of one experimental group and one control group. Data collection was carried out using a test instrument. Data analysis techniques included normality tests, homogeneity tests, and hypothesis testing.The results of the data analysis show that the FERA learning model had a significant effect on student learning outcomes. The test results yielded a significance value of 0.020. Since this value is less than the significance threshold (< 0.05), it can be concluded that there is a significant difference in the average scores between the experimental and control groups. These findings demonstrate that the use of innovative learning models such as FERA can contribute to improving students' academic performance, particularly in Islamic Religious Education.The FERA model successfully encouraged students to be more active and participative in the learning process, deepened their understanding of concepts, and fostered positive attitudes such as confidence and responsibility. This model also addresses the shortcomings of conventional teaching methods, which are often monotonous and fail to motivate students. Therefore, implementing the FERA model is highly recommended to make learning more innovative, meaningful, and aligned with Islamic educational values that emphasize reflection and the application of knowledge in daily life.This research is beneficial in helping students become more active learners, supporting teachers in selecting appropriate teaching models, and serving as a reference for other researchers in developing relevant instructional approaches.Top of Form